Ngafe Culture, Covid-19, and Sustainable Lifestyle: How the #ngopidirumah Becomes a New Trend during Pandemic - Devita, Marliani (I-Pop: International Journal of Indonesian Popular Culture and Communication, 2020)
The COVID-19 pandemic has changed people's lifestyles and daily habits due to social and physical distancing regulations to reduce the spread of the virus. Many people who usually hang out or ngafe cannot freely enjoy their favorite drinks in a cafe atmosphere. It inspired the #ngopidirumah movement on social media as a new lifestyle for coffee consumption, campaigned by local coffee industry players to adjust consumer activities during quarantine at home by providing products and services that facilitate ordering cafe-style coffee stocks. This article examines how the #ngopidirumah movement, applied by Anomali Coffee, shapes the trend of a cafe-style coffee lifestyle for consumers during a pandemic. Using a qualitative case study approach, data was obtained through in-depth interviews, online observation, and digital documentation on Instagram. The results of this study explain that the #ngopidirumah Movement, which Anomali Coffee applies to its consumers, forms a new trend of ngafe lifestyle at home, which refers to the dimensions of the consumer's lifestyle, namely activity, interest, opinion, and preserving the culture of community coffee consumption sustainably.